Understanding the role of real time digital simulator and the concept of power hardware in the loop in power system applications - Teo, How Kiat (2019)
Over the years, the improvement in technologies and the rising population in Singapore has resulted in an increasing demand for electricity. Based on improved electronic devices, the Real-Time Digital Simulator (RTDS) is built by OPAL-RT to provide power system solutions using a simulation technology that can be operated in a swift and accurate platform. This platform has the capability to simulate the actual electrical system and to produce a realistic output which is representative of an actual system. Through this project, the insight and data of the RTDS which facilitate the hardware in the loop (HIL) and power hardware in the loop (PHIL) testing are documented. Furthermore, using power amplifier as the setup for PHIL experiment, the Hybrid Energy Storage System (HESS) in a DC microgrid system is simulated. The bi-direction DC-DC converter and Lithium-Ion battery are utilized as hardware under test (HUT) and is connected to RTDS through the power amplifier. The closed-loop operation of the PHIL experiment is observed by implementing a variation in load demand and the renewable energy source. Hence, the PHIL simulation is not only able to test out the system hardware, but it can also assist in discovering the innovative and unique solutions for upcoming future load demand.